Frontispiece: Bright Electrogenerated Chemiluminescence of a Bis‐Donor Quadrupolar Spirofluorene Dye and Its Nanoparticles. Issue 36 (26th August 2016) - Li, Haidong; Daniel, Jonathan; Verlhac, Jean‐Baptiste; Blanchard‐Desce, Mireille; Sojic, Neso
Abstract : Electrogenerated Chemiluminescence Thiophene‐based materials have many outstanding chemical and physical properties, such as their unique variety of electronic properties and easy structure variation. A series of symmetric fluorescent dyes built from a spirofluorene core, bearing electroactive end‐groups and having different conjugated linkers were prepared in view of their use as building blocks for the preparation of electrochemiluminescent dyes and nanoparticles. The molecular confinement of the luminophores within fluorescent nanoparticles allows to design highly efficient bright nano‐emitters. For more details, see the Full Paper by M. Blanchard‐Desce, N. Sojic et al. onpage 12702 ff.